The Use of Learning Based on Various Learning Resources in Early Childhood Education - Fitria, Evy; Muslim, Suyitno; Solihatin, Etin (International Journal of Psychosocial Rehabilitation, 2020)
Learning in early childhood must be fun and not boring and must be able to stimulate the five senses of the child to do a lot of exploration through play activities. But the fact is there are still many teachers who provide learning that is far from the values of play. Teachers only rely on books as children’s activities, so that it looks like children’s learning is boring and does not use various existing learning resources. This paper aims to find out how the use of learning that uses various learning resources in early childhood education institutions that have used various learning resources in their learning. Besides this paper also aims to see how early childhood development has been facilitated by various learning resources in learning. The method in this research is qualitative. The results showed that the use of learning based on various learning resources was used in two activities by the teacher. First, the teacher uses various learning resources while discussing the theme of the day that is learned with the child. Second, the teacher has prepared a play environment where children explore in the child’s play area / play center for use by children. Observed, children who use many learning resources, their language development is more developed, children ask questions and tell their play experiences. In the fine motor aspect, children are increasingly coordinated eye and hand movements, in cognitive understanding, the ability to think more critically and the spirit of activity is very high. This research is expected to contribute to the world of early childhood education, especially teachers in designing learning to use various learning resources for children